THE INQUIRY OF INDEGENOUS CULTURE SEBAGAI MODEL PEMBELAJARAN MATA KULIAH PENDIDIKAN KEBUDAYAAN DAERAH UNTUK MENINGKATKAN KREATIFITAS MAHASISWA - Dhiniyati Gularso; Rosalia Susila Purwanti (Profesi Pendidikan Dasar, 2014)
nquiry model provides the opportunity for students to learn to develop their intellectualpotential in the fabric of the activities that he composed himself to find something.Students are encouraged to act actively seek answers to the problems it faces and drawtheir own conclusions through a process of critical scientific thinking, logical, and systematic.Students may not remain and be passive, receiving and memorizing lessonsgiven by the professor. The purpose of this study is students can explore the local cultureor indigenous wisdom-based inquiry learning culture through the Regional CulturalEducation courses to be included in the syllabus and lesson plans for each subject toelementary schools. Syllabus and lesson plans based on the indigenous culture is expectedto foster respect and appreciate the diversity of Indonesian culture. The methodused in this research is the development of research that approached by Research andDevelopment which refers to Thiaragajan (1994) with 4D models that define, design,develop and disseminate. The data required in this research is quantitative data andqualitative data. Acquisition of data using tests, observations, questionnaires. The instrumentsused are: (1) observation sheet subject of Pendidikan Kebudayaan Daerahfeasibility study using a model-based inquiry indigenous culture; (2) the observationsheet lecturer in organizing learning ability; (3 pieces of student activity observation;(4) The student questionnaire responses (5) the results of student competence. Analysisof the data in this study is a descriptive qualitative. These results are an average increaseof 76.54 kratifitas consisting of students above average creativity of students inanswering questions at 75.02 and accuracy measures inquiry learning at 76.17. 76.54Value proves that the research is successful because of the success criteria of this studywas 75. Based on these results it can be concluded that the Inquiry of indegenous Culturecan be used as learning models Regional Cultural Education Courses to enhancethe creativity of students. Sustainability of the student competency is learner-SD has thecharacter to Indonesia’s strong and cultured. Besides, it is also expected of students asprospective teachers to defend the Indonesian culture of the process of acculturationand globalization thus lowering the culture to learners after becoming a teacher someday.